PEMBELAJARAN DINI PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) DI SD NEGERI 001 PERHENTIAN RAJA - Nurhasanah Nurhasanah; Anindhita Wahyu Prameswari; Defti Oktavia; Ellya Syahfitri; Muhammad Alvin; Muhammad Arif Rahman; Muhammad Ariy Naufal; Novianty Ramadani Syam; Nurasifa Anisa; Ummul Athiyah; Qoriah Rahman (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2023)
Clean and healthy living behavior is a health behavior carried out by self-awareness. Implementing PHBS can be useful in improving health in the environment around the school. Education in children needs to be instilled from an early age, including teaching clean and healthy living behavior. One of the benefits is that children get used to doing this good thing, so that it carries over into adulthood. So the author aims to provide early learning regarding clean and healthy living behavior at SD Negeri 001 Perhentian Raja. This research uses descriptive research with research methods using several implementation stages, namely initial observation, providing direction and information and hand washing practices. Educational activities were followed enthusiastically until the activity was completed. Students are able to follow movements as examples of behavior that is classified as PHBS